Extracorporeal life support with an integrated left ventricular vent in children with a low cardiac output - Sandrio, Stany; Springer, Wolfgang; Karck, Matthias; Gorenflo, Matthias; Weymann, Alexander; Ruhparwar, Arjang; Loukanov, Tsvetomir (Cardiology in the young, 2014)
Background: The aim of this study was to evaluate our experience in central extracorporeal life support with an integrated left ventricular vent in children with cardiac failure. Methods: Eight children acquired extracorporeal life support with a left ventricular vent, either after cardiac surgery (n = 4) or during an acute cardiac illness (n = 4). The ascending aorta and right atrium were cannulated. The left ventricular vent was inserted through the right superior pulmonary vein and connected to the venous line on the extracorporeal life support such that active left heart decompression was achieved. Results: No patient died while on support, seven patients were successfully weaned from it and one patient was transitioned to a biventricular assist device. The median length of support was 6 days (range 5-10 days). One patient died while in the hospital, despite successful weaning from extracorporeal life support. No intra-cardiac thrombus or embolic stroke was observed. No patient developed relevant intracranial bleeding resulting in neurological dysfunction during and after extracorporeal life support. Conclusions: In case of a low cardiac output and an insufficient inter-atrial shunt, additional left ventricular decompression via a vent could help avoid left heart distension and might promote myocardial recovery. In pulmonary dysfunction, separate blood gas analyses from the venous cannula and the left ventricular vent help detect possible coronary hypoxia when the left ventricle begins to recover. We recommend the use of central extracorporeal life support with an integrated left ventricular vent in children with intractable cardiac failure.